Board diversity reforms: Do they matter for EU bank performance? - Arnaboldi, Francesca; Casu, Barbara; Kalotychou, Elena; Sarkisyan, Anna (My University, 2020)
We examine the impact of governance reforms related to board diversity on the performance of European Union banks. Using a difference‐in‐difference approach, we document that reforms increase bank stock returns and their volatility within the first 3 years after their enactment. The type of reform matters, with quotas increasing return volatility. The effectiveness of reforms depends on a country's institutional environment. The impact of reforms on return volatility is found to be beneficial in countries more open to diversity, with common law system and with greater economic freedom. Finally, reforms play a bigger role in banks that have ex ante less heterogeneous boards.
Keywords: Bank performance; Board diversity reforms; Corporate governance codes